Residual stress effect on link element of eccentrically braced frame. (January 2017) - Kurdi,; Budiono, Bambang; Moestopo, Muslinang; Kusumastuti, Dyah; Muslih, M. Refai
Abstract: The effects of residual stress on the performance of link elements as lateral force shield, particularly for earthquake load as in the Eccentrically Braced Frame (EBF), is the main focus of this research. Experimental tests were conducted in two stages: First, the residual stress measurement of the link element with Neutron Diffraction technique using the equipment of DN1 at Center of Science and Technology of Advanced Material - National Nuclear Energy Agency (PSTBM-BATAN); second, two links were tested, a standard link that corresponds with the AISC 341–10 and a modified link. Behaviors of both links were studied based on the residual stress distribution in the first stage. The magnitude of tensile stresses on and around the "k area" caused the initiation of crack on the standard link so that it decreases the performance of the link element. Modifications of the link by replacing the stiffener of the vertical web with the horizontal stiffener can avoid the initiation of crack that may occur on the web plate around the "k area" so that the performance of the link elements can be improved. Highlights: Residual stresses in k area of the link were measured using the neutron diffraction method. Magnitudes and distributions of the residual stresses were high on and around the k area of the link. Behaviors of standard or modified link elements due to cyclic loading were studied. The Addition of the horizontal web stiffeners may increase the performance of link elements.